Hubungan Lama Pendidikan dan Pengetahuan Ibu Tentang Gizi Seimbang Dengan Perilaku Pemberian Makan Anak Balita di Puskesmas Gilingan Surakarta - Asransyah, Asransyah; , Siti Zulaekah, A., M.Si; , Endang Nur Widyaningsih, S.ST. M.Si., Med (2016)
Feeding behavior is an important factor for the growth of under five children. Feeding practice in children can be influenced by mother's knowledge and attitude. Education and knowledge are indirect factors affecting someone's behaviour. Nutritional knowledge supported by adequate education will inculcate the habit and the use of a healthy food. To determine the relationship of mother's education and knowledge on balanced nutrition to feeding behavior of under five children at gilingan primary health care of surakarta. This study was a quantitative research with cross sectional design used had 46 mothers as respondents which obtained by simple random sampling data of education. Knowledge, and behavior were obtained through direct interview. Data was analyzed using pearson product moment and rank spearman (for abnormal data). Most of the respondent had secondary education level 73.9%. The level of mother's knowledge on balanced nutrition was medium 58.7%. Feeding behavior of the respondent mostly categorized as medium, with the prevalence of 84.8%. Statistical analysis on the relationship between mother's education feeding behavior was resultrs in p=0.001, while the relationship between knowledge on nutrition and feeding practices was resultrs in p=0143. There is a relationship beetwen mother's education and feeding behaviour in under five children at gilingan primary health care of surakarta. There is no relationship between mother's knowledge on balanced nutrition with feeding behaviour in under five children at gilingan primary health care of surakarta.